Wafer-Scale Growth of 3D Graphene on SiO2by Remote Metal Catalyst-Assisted MOCVD and Its Application as a NO2Gas Sensor - Nasir, Tuqeer; Kim, Bum Jun; Lee, Sang Hoon; Jeong, Byung Joo; Cho, Sooheon; Lee, Bom; Yoon, Sang Ok; Jang, Han Eol; Yu, Hak Ki; Choi, Jae Young (Crystal Growth and Design, 2022)
Chemical vapor deposition (CVD) of graphene on catalytic metal substrates is the most common and widely used method for the uniform growth of graphene. However, this method is limited to large-scale applications because of the requirement of an additional step of transferring CVD graphene to required substrates. The direct growth of graphene-based materials on arbitrary substrates is essential to completely realize the full potential of graphene's exceptional electrical and chemical properties. In this study, we provide a novel approach for metal-organic chemical vapor deposition (MOCVD) of uniform graphene-based three-dimensional (3D) nanostructures on SiO2/Si substrates. This new method of MOCVD graphene growth eliminates the tedious process of graphene transfer, which introduces a number of defects and impurities. During the MOCVD growth step, an organometallic precursor, bis(t-butylacetoacetato) Cu(II) (Cu(tbaoac)2), was used to supply the airborne copper catalyst owing to its higher sublimation rate at lower temperatures. This new approach results in uniform deposition of graphene on SiO2/Si, and the morphology of the deposited films can be controlled by varying the growth time and the type of copper catalyst. This 3D graphene structure, which has a high surface area, may be used in several applications like a highly selective NO2gas sensor.
Keywords: 3D graphene; Catalytic metals; Chemical vapor deposition graphene; Chemical vapour deposition; Copper catalyst; Gas-sensors; ITS applications; Metal catalyst; Metal-organic chemical vapour depositions; Wafer scale